Assessing the Effects of Entrepreneurial Attributes and Business Practices on the Continuing Existence of Small and Medium Enterprises (SMEs) Using Deming Management Model of Total Quality as a Benchmark - Owusu, Eric Edwin; Bonsu, Charles Akomea; Owusu, Alfred; Ofori, Daniel; Brefo-Manuh, Adwoa Benewaa (Business and Economic Research, 2022)
<p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Entrepreneurship is certainly not a simple job and does not generally ensure a 100% achievement. Numerous basic features must be set up to empower entrepreneurs to attain a proportion of progress. SMEs therefore deserve attention, especially with regards to the entrepreneurial attributes as well as the business practices of the entrepreneur. The study investigates the effect entrepreneurial features and business practices on the continuing endurance of SMEs. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Descriptive research method was employed to obtain a picture of the effect of entrepreneurial features as well as corporate practices on the continuing endurance of SMEs in Ghana. A mixed method strategy was employed to reach conclusions that are accurate, reliable and reproducible. The population of the study focused on entrepreneurs in the small, medium and large enterprises in the Kumasi metropolis. In all, 100 questionnaires distributed, the researchers were able to retrieve 90 representing 90% of the response rate. Interviews, as well as questionnaires, were the main intruments utilised to gather the required information for the study. <p class="ber-body" style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Findings revealed that entrepreneurs require to have some entrepreneurial qualities for continuing endurance and that specific attributes make some entrepreneurs more fit to maintaining a fruitful business than other, the principle on which this research work concludes. It was realised that characteristics, values and assumptions of entrepreneurs in SMEs may impact their selection of management practices and consequently the presentation of their firms. The crucial determinant for the adoption of Deming Management Model of Total Quality in SMEs is to intensify awareness and motivate all workers on satisfying clients. It was further revealed that Creativity, Self-assurance, and Ability to Adapt negatively influence Teamwork, Risk Management and Planning of business activities among the SMEs surveyed.